Research and Application of Core Technology of Storm Surge Prevention Ecological Seawall in Guangdong-Hong Kong-Macao Greater Bay Area - CAO Chunding; WANG Meng; TANG Le (Renmin Zhujiang)
In the design of the ecological seawall project for storm surge prevention on the north coast of Lingshan Island in the Greater Bay Area, to solve the contradiction between urban flood tide prevention and the hydrophilicity of the coastal landscape ecological seawall, the design is transformed from the traditional single tidal wave prevention seawall to the diversified coastal landscape ecological seawall by the concept of innovative technology. This paper innovatively proposes the following two technologies: the multi-stage wave dissipation platform technology and the upstream drainage system technology of coastal landscape belts to solve the problem of wave dissipation and drainage. In practice, the paper proposes the concepts of "horizontal for vertical" and "external drainage of external water and internal drainage of internal water" to break the traditional "blocking" and "resisting" of seawalls to the waves. It adopts the horizontal multi-stage wave dissipation platform technology to eliminate the waves and sets up a multi-stage drainage system to realize the self-exhaustion of the waves. The flexible articulation of "pass" and "discharge" for the waves on the waterfront can effectively reduce the vertical dike top elevation to solve the problem of "dike surrounding the city" and realize the purpose of coastal landscape ecological seawall. The research results have been applied to the project and have been tested by several storm surges to prove that the expected results have been achieved. In terms of the resilient city, especially in the design of the ecological dike, Lingshan Island exchanges the width for the height, which can not only prevent floods but also meet the requirements of water, leisure, and landscape. It provides experience and reference for the Lingnan region of ecological construction, and even the same type of construction in China's coastal estuarine areas.